2018
DOI: 10.1111/jonm.12540
|View full text |Cite
|
Sign up to set email alerts
|

Policy to practice: Investment in transitioning new graduate nurses to the workplace

Abstract: Responding to the needs of new graduate nurses has potential long-term advantages for health care organisations and can influence both quality and delivery of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 22 publications
3
42
0
Order By: Relevance
“…From the sociodemographic data, it was observed that the participants of this study were predominantly young adults, whites and females. Corroborating this result, further research ( 5 , 17 - 18 ) carried out with Nursing graduates have indicated the predominance of women and the average age group below 32 years.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…From the sociodemographic data, it was observed that the participants of this study were predominantly young adults, whites and females. Corroborating this result, further research ( 5 , 17 - 18 ) carried out with Nursing graduates have indicated the predominance of women and the average age group below 32 years.…”
Section: Discussionmentioning
confidence: 76%
“…Globally, international studies ( 17 - 19 ) highlight the growing insertion of women under the age of 30 in the world of work, with emphasis on Nursing in the health area. However, regarding employability, Nursing has experienced a demand for jobs below the market’s offer in the South and Southeast regions of the country ( 20 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the length of transition programmes varies from 1 month up to 36 months, and the common features of these programmes are a defined resource person, mentorship and peer support opportunities (15). Transition programmes develop NGNs’ organising and prioritising skills, communication and leadership abilities (12,14,16), and competence (17,18). NGNs participating in formal transition programmes have a smoother transition into clinical practice (12).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies were conducted to evaluate the effect of government supported extended orientation on new graduate nurse transition to work (Baumann, Hunsberger, & Crea-Arsenio, 2011Baumann, Hunsberger, Crea-Arsenio, & Akhtar-Danesh, 2018;Baumann et al, 2016). Results demonstrate the initiative-provided employers with the resources to not only hire but also support the transition of new nurses into specialty acute care via extended orientation.…”
mentioning
confidence: 99%